MOBILE MEASUREMENTS WITH BICYCLES: A SYSTEMATIC REVIEW APPLIED TO THE THERMAL ENVIRONMENT OF URBAN MICROCLIMATES - Writzl, Luana; Wollmann, Cassio Arthur; Costa, Iago Turba; Iensse, Amanda Comassetto; da Silva, Aline Nunes; Baumhardt, Otavio de Freitas; da Silva, Robson Rigão; da Costa, Tarcisio Oliveira; Gobo, João Paulo Assis; Shooshtarian, Salman; et al. (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
This study concerns in to collect, via a systematic review, papers from international academic researches that employed bicycles only to collect primary data on environmental variables for research on microclimatic thermal problems in urban contexts and others. Three international article search platforms were used. After reading the titles, abstracts, and entire works, 13 articles were chosen that employed bicycles in their mobile transects between 2011 and 2023. The analytical methodologies connected them to the thermal environment employed by the research, such as the primary characterizers of urban morphology, were visible from this. It is worth emphasizing that, while the platforms offer outstanding results in terms of article discovery, it is know that there are additional publications that employed similar technique but did not appear in the platforms’ results. Six more items were discovered that were absent from the chosen search engines. It is significant to observe that, after looking over the 19 articles, the most part of them were only released in the past 25 years, with the oldest being found in 1998. Research has indicated that the use of bicycles to collect environmental data is related to the possibility that bicycles are more accessible than cars and more safety than walking along cities, moreover, this approach is less expensive. Apart from the several benefits that studies utilizing this methodology observed, it is believed that bicycles would be a more environmentally responsible and sustainable mode of transportation than alternatives. In this manner, it is hoped that additional research utilizing the effective mobile measurement technique with bicycles would be carried out in the future.